1997
DOI: 10.1164/ajrccm.155.6.9196113
|View full text |Cite
|
Sign up to set email alerts
|

Yield of computed tomography and bronchoscopy for the diagnosis of Mycobacterium avium complex pulmonary disease.

Abstract: Mycobacterium avium complex (MAC) pulmonary disease with nodules and bronchiectasis is increasing. But the usefulness of computed tomography (CT) and bronchoscopy for diagnosis and the significance of MAC isolation from respiratory secretions are still unclear. For a 4-yr period, we prospectively examined the role of bronchoscopy with bronchial washing and transbronchial lung biopsy in 26 patients who had clusters of small nodules in the periphery of the lung associated with ectatic changes of the draining bro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
105
1

Year Published

1998
1998
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 151 publications
(110 citation statements)
references
References 0 publications
0
105
1
Order By: Relevance
“…Recently, the disease has become prevalent in elderly females without predisposing bronchopulmonary illness. Characteristic CT findings of MAC pulmonary disease are clusters of small nodules in the subpleural regions of the lung in combination with dilated changes of the bronchi [6]. Between 1990 and 1997, 210 patients with MAC pulmonary disease were seen in the author's hospital and a variety of fungi were concurrently isolated from 10 patients: Aspergillus fumigatus (6), Aspergillus niger (2), S. apiospermum (2), Schizophyllum commune (1) and Exophiala dermatitidis (1) (unpublished data).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the disease has become prevalent in elderly females without predisposing bronchopulmonary illness. Characteristic CT findings of MAC pulmonary disease are clusters of small nodules in the subpleural regions of the lung in combination with dilated changes of the bronchi [6]. Between 1990 and 1997, 210 patients with MAC pulmonary disease were seen in the author's hospital and a variety of fungi were concurrently isolated from 10 patients: Aspergillus fumigatus (6), Aspergillus niger (2), S. apiospermum (2), Schizophyllum commune (1) and Exophiala dermatitidis (1) (unpublished data).…”
Section: Discussionmentioning
confidence: 99%
“…As mentioned earlier, in patients with bronchiectasis with suggestion of MAC on HRCT Tanaka et al found that 10/26 who underwent transbronchial lung biopsy had granuloma formation, 8 of whom were positive for MAC and 2 were positive for M. abscessus and M. fortuitum. They showed that this was present with infection and not with colonization (Tanaka, E. 1997).…”
Section: Role Of Endobronchial and Transbronchial Biopsy In Bronchiecmentioning
confidence: 99%
“…They also found comparable sensitivities between both BAL and protected specimen brush. Tanaka et al found that bronchial washings was twice as sensitive as expectorated sputum for isolation of Mycobacterium avium complex (Tanaka, E. 1997). They also went on to show that granuloma formation as seen on lung biopsy would suggest infection rather than colonization.…”
Section: Role Of Diagnostic Bronchoscopy In Bronchiectasismentioning
confidence: 99%
“…16 Studies show that in patients with MAC pulmonary disease, cultures from bronchial lavages have a greater sensitivity than sputum cultures; positive cultures were present in 93.8% and 50% of bronchial washings compared to 64.3% and 23.1% of sputum samples, respectively. 74,75 In suspected cases of LWS with three negative sputum samples, bronchoscopy with bronchial washings may be needed to confirm the diagnosis. Recently, polymerase chain reaction (PCR) and serodiagnostic tests have been utilized for rapid diagnosis.…”
Section: Pathogenesismentioning
confidence: 99%